2018
DOI: 10.1016/j.cgh.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Clinical, Endoscopic, and Histologic Outcome Measures and Placebo Response Rates in Clinical Trials of Eosinophilic Esophagitis: A Systematic Review

Abstract: In a systematic review of the literature, we found that no standardized definitions of histologic, endoscopic, or patient-reported outcomes are used to determine whether pharmacologic agents produce a response or remission in patients with EoE. A core outcome set is needed to reduce heterogeneity in outcome reporting and facilitate trial interpretation and comparison of results from trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…EoE researchers, patients and other stakeholders will arrive at a core outcome set, including symptomsbased PRO, that will be used in RCT, observational studies and clinical practice [21]. However, assessing only dysphagia frequency in all types of studies might be too simplistic of an approach.…”
Section: Resultsmentioning
confidence: 99%
“…EoE researchers, patients and other stakeholders will arrive at a core outcome set, including symptomsbased PRO, that will be used in RCT, observational studies and clinical practice [21]. However, assessing only dysphagia frequency in all types of studies might be too simplistic of an approach.…”
Section: Resultsmentioning
confidence: 99%
“…7 All these trials had a primary endpoint based exclusively on symptoms, with no objective evaluation. 7 The high and unpredictable placebo response rates have been noted in many other chronic diseases, including chronic constipation, 8,9 eosinophilic esophagitis, 10,11 and nonalcoholic fatty liver disease, 12,13 among others.…”
mentioning
confidence: 99%
“…The placebo arms of randomized controlled trials of swallowed topical corticosteroids (STCs) for EoE also have shown no substantial changes in esophageal eosinophil counts, supporting this concept, although these findings were over a much shorter time course. 5,6 In addition, a large retrospective cohort study showed that almost no children "grow out of" EoE, 7 other studies have shown that disease recurs after nonsteroid therapies as well, 8,9 and a study in adults showed that less than 2% of those who achieved "deep remission" (no symptoms, endoscopic findings, or histologic findings for at least 6 months) could discontinue STCs in the long term; all other patients relapsed after a median of only 22 weeks of discontinuing therapy. 10 A key issue with any chronic disease is understanding the long-term consequences of that disease were it not to be treated.…”
mentioning
confidence: 99%